Polymer scaffolds with no skin-effect for tissue engineering applications fabricated by thermally induced phase separation - Kasoju, Naresh; Kubies, Dana; Sedlačík, Tomáš; Janoušková, Olga; Koubková, Jana; Kumorek, Marta M; Rypáček, František (Biomedical materials, 2016)
Thermally induced phase separation (TIPS) based methods are widely used for the fabrication of porous scaffolds for tissue engineering and related applications. However, formation of a less-/non-porous layer at the scaffold's outer surface at the air-liquid interface, often known as the skin-effect, restricts the cell infiltration inside the scaffold and therefore limits its efficacy. To this end, we demonstrate a TIPS-based process involving the exposure of the just quenched poly(lactide-co-caprolactone):dioxane phases to the pure dioxane for a short time while still being under the quenching strength, herein after termed as the second quenching (2Q). Scanning electron microscopy, mercury intrusion porosimetry and contact angle analysis revealed a direct correlation between the time of 2Q and the gradual disappearance of the skin, followed by the widening of the outer pores and the formation of the fibrous filaments over the surface, with no effect on the internal pore architecture and the overall porosity of scaffolds. The experiments at various quenching temperatures and polymer concentrations revealed the versatility of 2Q in removing the skin. In addition, the in vitro cell culture studies with the human primary fibroblasts showed that the scaffolds prepared by the TIPS based 2Q process, with the optimal exposure time, resulted in a higher cell seeding and viability in contrast to the scaffolds prepared by the regular TIPS. Thus, TIPS including the 2Q step is a facile, versatile and innovative approach to fabricate the polymer scaffolds with a skin-free and fully open porous surface morphology for achieving a better cell response in tissue engineering and related applications.
Keywords: Equipment Design; tkáňové podpůrné struktury; chemická frakcionace; analýza selhání vybavení; biokompatibilní materiály; Phase Transition; vytápění; Heating; poréznost; povrchové vlastnosti; Polymers; tkáňové inženýrství; Equipment Failure Analysis; Polyesters; Porosity; Biocompatible Materials; Materials Testing; testování materiálů; polymery; změna skupenství; Tissue Engineering; design vybavení; polyestery; Chemical Fractionation; Tissue Scaffolds; Surface Properties